Sarana Prasarana dan Keefektifan Pelayanan: Evaluasi Kinerja pada Laboratorium Bisnis Politeknik Negeri Bandung - Tita Adysti; Fauzan Hammam Da’watudin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Technological advancements in the retail sector require vocational education institutions to provide practical learning environments that accurately reflect real industry operations. The Business Laboratory at Politeknik Negeri Bandung is designed as a training facility where students engage directly in retail service activities, including cashier operation, product display arrangement, and customer interaction. Therefore, the quality of facilities within this laboratory plays a crucial role in supporting students’ service performance during practical sessions. This study aims to evaluate the condition of the facilities provided in the Business Laboratory and examine their role in enhancing the effectiveness of student-led services. A quantitative approach with descriptive and verificative methods was employed by distributing questionnaires to actual customers who shop at the laboratory. The results indicate that physical facilities and operational equipment function well and assist students in delivering faster, more accurate, and more comfortable services. However, certain supporting facilities and inventory management aspects still require improvement to ensure a better customer experience. Overall, this study highlights that continuous and adaptive facility management is essential to align vocational practice with technological developments in the retail industry and to prepare students as competent future professionals capable of meeting workplace demands